Perancangan Interior Art Development and Activity Center di Surabaya - Angeline, Vanya; Yong, Sherly de; Mulyono, Hendy (Intra, 2018)
Creative Economy is a topic that is being discussed by the public. Creative economy industry is a way to face the current development and the nation’s economy. Since the existence of creative economy industry, art and creativity become something that is appreciated by the nation and state. The design of Art Development and Activity Center in Surabaya is aimed to accommodate adolescent learning activities as a medium to develop creativity and education in the field of art in order to face creative industry. Such places are necessary nowadays because a lot of Indonesian people are still lacking of knowledge, especially in the field of art. Therefore, this problem can affect the enthusiasm to develop in the field of creative economy. The design of Art Development and Activity Center can be regarded as a place for art course facility in the field of applied art, which are interior design, fashion design, visual communication design, product design (jewelry design), and music. Moreover, this place is also equipped with facilities that can support learning activities and express art such as mini gallery and mini auditorium. Interior design of Art Development and Activity Center in Surabaya is also supported with its interior organization that applies the Modern Pop Art Contemporary style so that it will radiate the nuance of art. This design uses 6 steps of method, which are empathize & define, research, ideate, prototype, test, and implementation.